2017
DOI: 10.1590/1678-4685-gmb-2016-0110
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel mutation in ARSA gene in three patients of an Iranian family with metachromatic leukodystrophy disorder

Abstract: Metachromatic leukodystrophy disorder (MLD) is an autosomal recessive and lysosomal storage disease. The disease is caused by the deficiency of the enzyme arylsulfatase A (ARSA) which is encoded by the ARSA gene. Different mutations have been reported in different populations. The present study was aimed to detect the mutation type of the ARSA gene in three relative Iranian patients. We found a novel homozygous missense mutation c.1070 G > T (p.Gly357Val) in exon 6 of these patients. The mutation was found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…False-negative MLD diagnosis could result in withholding treatment opportunities for otherwise eligible patients, especially since experimental therapies including gene therapy and intrathecal enzyme-replacement therapy are evolving. More phenotype information on pathogenic ARSA variants will also help interpreting results from the pilot [31,32]. Finally, Narayanan et al recently reported 36 ARSA variants in MLD patients from India, and no less than sixteen of them were novel [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…False-negative MLD diagnosis could result in withholding treatment opportunities for otherwise eligible patients, especially since experimental therapies including gene therapy and intrathecal enzyme-replacement therapy are evolving. More phenotype information on pathogenic ARSA variants will also help interpreting results from the pilot [31,32]. Finally, Narayanan et al recently reported 36 ARSA variants in MLD patients from India, and no less than sixteen of them were novel [33].…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, novel ARSA variants in previously less frequently studied ethnicities are increasingly reported. A few examples are the c.847G > A, p.(Asp283Asn), c.853G > A, p.(Asp285Asn), and c.1031C > A, p.(Ala344Asp) variants in Sri Lanka [ 27 ]; the c.256C > G, p.(Arg86Gly), c.344 T > C, p.(Leu115Pro), and c.693C > A, p.(His231Gln) variants in respectively Jordan, Pakistan, and Tunisia [ 28 – 30 ]; and the c.1070G > T, p.(Gly357Val), c.585G > T, p.(Trp195Cys), c.849C > G, p.(Asp283Glu), and c.911A > G, p.(Lys304Arg) variants in Iran [ 31 , 32 ]. Finally, Narayanan et al recently reported 36 ARSA variants in MLD patients from India, and no less than sixteen of them were novel [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the theoretical 3D structural model showed that deletion of the Guanine nucleotide generates a premature stop codon and therefore a nonfunctional protein, in which the amino acid Histidine at position 140 is modi ed by an isoleucine (H140I) (7). The mutation found is correlated with the heterozygous variant used as a positive control in the identi cation of childhood MLD according to the study by McCreary et al, 2019 (24), a cohort study that included 60 children with suspected genetic neuroin ammation for which a sequencing panel directed at 257 genes was developed, in which a molecular diagnosis was veri ed in 20% of the patients, highlighting some unexpected genotype-phenotype associations and new pathogenic variants.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, approximately 200 different types of mutations are known (6). Most of these are missense and, therefore, lead to de cient expression or structural damage to the enzyme Arylsulfatase A (ARSA) (7). ARSA is a lysosomal hydrolase that catalyzes the rst step in the degradation of cerebroside 3 sulfate, one of the sulfatides found mainly in the white matter of the CNS and SNP (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…MLD (OMIM # 250100) is a lysosomal storage disorder with an autosomal recessive pattern of inheritance, so carriers of one copy of the abnormal gene are not affected by the disease 18,19 . MLD is caused by mutations in the ARSA gene, located on chromosome 22q13.33 20 , that encodes the lysosomal enzyme Arylsulfatase A (ARSA) (ARSA; OMIM 607574, GenBank accession number, NG_009260) 21,22 .…”
Section: Metachromatic Leukodystrophy (Mld)mentioning
confidence: 99%